Durable graphene-coated bipolar plates for polymer electrolyte fuel cells. (2nd November 2017) - Lee, Yoon Ho; Noh, SeungTak; Lee, Ju-Hyung; Chun, Seung-Hyun; Cha, Suk Won; Chang, Ikwhang
Abstract: In this paper, we investigate the role of a graphene layer for polymer electrolyte fuel cells (PEFCs) which require an ultrathin protective layer for copper bipolar plates. The graphene layer was deposited by chemical vapor deposition using CH4 at 830 °C. We examined the deposited graphene layer to characterize microstructural properties using a Raman spectroscopy microscope and a secondary electron microscope. During the electrochemical tests, the current–voltage–power (I–V–P) performance of the single cell using the copper bipolar plate with the graphene layer was highly stable for 5 h, while the I–V–P performance of the single cell using the pure copper bipolar plate (without the graphene layer) was much lower. We conclude that the graphene layer acts as a very thin passivation layer on the copper bipolar plate of a PEFC. Highlights: A graphene layer on copper bipolar plate is deposited by chemical vapor deposition. The graphene layer was deposited by chemical vapor deposition using CH4 at 830 °C. The graphene on the copper bipolar plate acts as a very thin passivation layer.